DIAGNOSA DARAH SEBAGAI INDIKATOR KESEHATAN IKAN BETOK (Anabas testudineus Bloch), IKAN LELE (Clarias batracus) DAN IKAN PATIN (Pangasius hypopthalmus) - Rimalia, Anny; Kisworo, Yulius (Universitas Dr Soetomo, 2021)
The One of the factors that influence the business of aquacultur is fish disease. For thisreason, it is necessary to carry out laboratory diagnosis of fish diseases to determine the healthstatus of fish and normal standards of fish blood picture. The research method used wasdescriptive with samples of Betok fish (Anabas testudineus Bloch), catfish (Clarias batracus),and catfish (Pangasius hypopthalmus) from fish traders at Banjarbaru market, with the observedhealth variables namely blood components Hematocrit (Hct), Erythrocytes (RBC). andhemoglobin (Hb). The results of the research for Betok fish (Anabas testudineus Bloch)obtained the value of Hct = 39%, RBC = 3.52 X106/mm3, Hb = 5.60 gr/dl. Catfish (Clariasbatracus) Hct=33,28%, RBC= 4,5x106/mm3, Hb=7.03 gr/dl. Patin (Pangasius hypopthalmus)obtained the value of Hct=24%, RBC=2,9X106/mm3, Hb=7.0 gr/dl. For the three types of fish,the Hematocrit (Hct) and Hemoglobin (Hb) parameters were still within normal limits. Then theerythrocyte (RBC) value of Betok fish (Anabas testudineus Bloch) was still within the normalthreshold. while the Erythrocyte (RBC) value of catfish (Clarias batracus) and catfish (Pangasiushypopthalmus) was higher than the normal limit so that the picture of catfish (Clarias batracus)and catfish (Pangasius hypopthalmus) experienced stress which was thought to be due tohandling when marketed